Methods to improve the recruitment of holm-oak seedlings in grazed Mediterranean savanna-like ecosystems (dehesas) - Leiva, María José; Mancilla-Leyton, Juan Manuel; Martín-Vicente, Ángel (Annals of Forest Science, 2012)
& Context “Dehesas” are savanna-like ecosystems of human origin that extend broadly in the Mediterranean area of the Iberian Peninsula. They consist of scattered oaks (mainly Quercus ilex subsp. ballota L. holm-oak), an annual grassland layer and interspersed shrubs. These ecosystems, used for grazing and wild game, support high plant and animal biodiversity and provide important environmental services. At present, Mediterranean “dehesas” are endangered by the lack of oak regeneration. & Aims This paper analyses the efficiency of: (1) using shrubs as nurse plants; (2) drip irrigation of seedlings during summer; and (3) a combination of the two methods for the restoration of a “dehesa” in a mid-mountain Mediterranean area of southern Spain. & Methods Different techniques were tested to improve the recruitment of holm-oak seedling during a 3-year field experiment: (1) acorn plantation in open spaces, irrigating seedlings during the first dry season; (2) acorn plantation beneath the canopy of Myrtus communis L. and (3) both methods combined. & Results There was a large facilitative effect of myrtle for the recruitment of holm-oak seedlings, regardless of the supply of irrigation. This effect was associated with a large decrease in air temperature and photosynthetically active radiation beneath myrtle canopies. By contrast, summer irrigation of seedlings planted in open spaces did not improve seedling survival after 3 years despite a small and transient positive effect on seedling survival during the 1st year. & Conclusion The use of evergreen shrubs, such as myrtle, as nurse plants may be considered to restore “dehesas” instead of expensive seedling irrigation techniques. Several studies have promoted abandoning grazing to increase holm oak selfregeneration in “dehesas”. However, creating closed patches of naturally occurring evergreen shrubs could provide suitable sites for oak planting when necessary, thus enhancing seedling recruitment without damaging the environmental and economic value of these ecosystems.
Keywords: nurse plant; Photosynthetically active radiation; seedling emergence timing; seedling longevity; summer drip-irrigation of seedlings